1994
DOI: 10.1007/bf01052726
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in brain tumors

Abstract: Resistance to chemotherapy in brain tumors is complex and may involve multiple mechanisms. For commonly used drugs, such as nitrosoureas and platinum compounds, major mechanisms may involve increaded DNA repair or removal of the drug-DNA adducts. For water soluble nitrosoureas and also for platinum compounds, other mechanisms, such as alteration in drug transport, may be important. Another major mechanism may involve glutathione and glutathione-S-transferase pathways. For vinca alkaloids and epipodophyllotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 60 publications
0
44
0
Order By: Relevance
“…In our study, we observed that combined treatment of glioma cells with chemotherapy drug TMZ and CDK6 shRNA significantly inhibited cell growth, which is more effective than single treatment either with TMZ or CDK6 shRNA. The mechanism underlying chemotherapy-resistance of glioma has been intensively studied (18,19,21,22). Many drugresistant genes have been found, which mainly belongs to DNA repair enzymes, small-molecule transmembrane transporters and drug metabolism proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed that combined treatment of glioma cells with chemotherapy drug TMZ and CDK6 shRNA significantly inhibited cell growth, which is more effective than single treatment either with TMZ or CDK6 shRNA. The mechanism underlying chemotherapy-resistance of glioma has been intensively studied (18,19,21,22). Many drugresistant genes have been found, which mainly belongs to DNA repair enzymes, small-molecule transmembrane transporters and drug metabolism proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low permeability of drugs across blood-brain barrier reduced drug concentration in cerebral-spinal fluid. On the other hand, glioma cell are resistant to chemotherapy treatment, mainly due to high activity of DNA repair mechanism, tolerance to cell cycle check points, reduced uptake of drug and quick metabolism of drug molecules (18)(19)(20).…”
Section: Enhanced Chemotherapy Effect Of Tmz On Cdk6-knockdown Gliomamentioning
confidence: 99%
“…Pgp, MRP1, MRP2 and MRP3 share the property of transporting common substrates such as vincristine and etoposide, 2 anticancer drugs widely used in the treatment of human brain tumours. 1,9 Today, it seems relevant to question whether MRP1, MRP2 and MRP3 are involved in the MDR phenotype of human cancer cells where they are overexpressed. 6,10,11 In contrast, high MRP5 expression in some lung cancer cell lines is not correlated with the level of resistance of these cell lines against drugs involved in the MDR phenotype such as vincristine or doxorubicin.…”
mentioning
confidence: 99%
“…A number of mechanisms may contribute to cellular drug resistance, such as reduced intracellular drug concentrations, rapid inactivation of the drug by induction of certain enzyme systems and increased rate of DNA repair. 1) Dysregulation of apoptosis, a genetically controlled form of cell death, may also be important for drug resistance because the mechanism by which most chemotherapeutic agents induced cell death appeared to be apoptosis. 2) Identification of the gene related to apoptosis and gene products and investigation of the mechanisms of the apoptotic regulation have laid a foundation for the discovery of new drugs.…”
mentioning
confidence: 99%